Association Levels of Development the City of Kerman In Terms of Health and Indicators Using the Numerical Taxonomy - Mehdi Raadabadi; Mohsen Barouni; Reza Goudarzi; Najmeh Baghian; Asma Sabermahani (Shahid Sadoughi University of Medical Sciences, 2015)
Abstract Introduction: knowledge and understanding of the situation is necessary for planning to achieve optimal development that this identifying involves separating study regions to planning areas and evaluation of the separate regions by development indicators and analysis and ranking of each area in terms of having development blessings. This study aims to Stratification of Kerman Province Districts in Terms of Health Indicators with taxonomy models. Materials & Methods: This descriptive study was applied using taxonomy Models to Stratification of 16 Kerman Province Districts based on 10 selected health indicators. Data were collected by the researcher form and through statistical center of Iran and Kerman University of Medical Sciences. Data analysis was done using SPSS/19. Results: The calculations based on taxonomy Model, Baft district with 0.46 and Rigan district with 0.96 were most and less developed districts, respectively. Conclusions: there is a relatively large difference between cities in the health sector and Most of the citiesare not satisfactory in the aspect of healthcare indices. So having plan on how to allocate resources for the health sector to improve the health of the cities is essential for policy makers.